Sustainability development through green economics - Taneja, Sanjay; Kumar, Pawan; Reepu; Balusamy, Balamurugan; Sood, Kiran; Grima, Simon (Contemporary studies in economic and financial analysis, 2024)
Our economies currently encourage excessive consumerism, weakening social ties, and depleting natural resources. Unfortunately, this is just the way economies have been developing. However, it is neither inevitable nor necessary. It takes a fresh economic vision to address these issues: a Green Economy. The concept of a "green economy" does not supplant sustainable development but instead places a fresh emphasis on a region's economy, investments pertaining to infrastructure, job and skill needs, and favourable social and environmental consequences. Sustainability Development through Green Economics examines sustainable finance, green tourism, green marketing as a tributary towards sustainable development. The multidisciplinary chapters traverse the power of economic as well as financial policy, green investment, green insurance as well as green infrastructural development to ensure sustainable development. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.